Association of Electrocardiographically Determined Left Ventricular Mass With Incident Diabetes, 1985–1986 to 2010–2011: Coronary Artery Risk Development in Young Adults (CARDIA) study - Carnethon, Mercedes R. (American Diabetes Association, 2013)
OBJECTIVE: Electrocardiographic indices reflecting left ventricular hypertrophy are associated with incident diabetes in clinical populations at risk for coronary heart disease. We tested whether electrocardiographically determined left ventricular mass was positively associated with incident diabetes in a population sample. RESEARCH DESIGN AND METHODS: Coronary Artery Risk Development in Young Adults (CARDIA) study participants (n = 4,739) were followed from 1985–1986 to 2010–2011 for incident diabetes. Validated sex- and race-specific formulas were applied to standard electrocardiograms to determine left ventricular mass. RESULTS: Over 25 years, 444 participants developed diabetes (9.4%). After adjustment for demographic, behavioral, and clinical covariates, participants in the highest quartile of left ventricular mass index (LVMI) were twice as likely to develop diabetes than participants in the lower three quartiles (hazard ratio 2.61 [95% CI 2.16–3.17]). Neither Cornell voltage nor Cornell voltage product was associated with incident diabetes in fully adjusted models. CONCLUSIONS: Electrocardiographically determined LVMI may be a useful noninvasive marker for identifying adults at risk for diabetes.